THE NEW ERA OF BROWSING -VOICE BROWSING (International Journal of Engineering and Computer Science, 2012)
The technology of voice browsing is rapidly evolving these days. It is because the use of cellphones is increasing at a very high rate, as compared to connected PCs. Listening and speaking are the natural modes of communication and information gathering. As a result we are now heading towards a more voice based approach of browsing rather than operating on textual mode. This paper concentrates on this new technique, voice browsing, which unites speech recognition and speech synthesis that can be very fruitful in the coming years.